2014
DOI: 10.1074/jbc.m113.511311
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Cell Proliferation and Senescence Are Regulated by Receptor Guanylyl Cyclase C and p21

Abstract: Background:Receptor guanylyl cyclase C regulates ion secretion and cytostasis in intestinal epithelial cells. Results: Ligand-mediated activation of guanylyl cyclase C and subsequent elevation of cGMP increase levels of p21 via PKGII and p38 MAPK. Conclusion: Guanylyl cyclase C can induce intestinal epithelial cell cytostasis and senescence via p21. Significance: Intestinal neoplasia is controlled by cGMP and p21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 66 publications
(67 reference statements)
3
39
0
Order By: Relevance
“…Next, flow cytometric analysis revealed that downregulation of FALEC might contribute to the cell arrest in G1/G0 phase of cell cycle. P21 are family members of cyclin‐dependent kinase inhibitors, which is responsible for arresting cells in G1 phases and negatively control cell proliferation, acting as tumor suppressor . In the present study, cells with down regulation of FALEC leads to increased level of p21 and relative change of downstream CKI and cyclin, indicating that FALEC exerts its oncogenic function at least in part via suppressing of p21 expression.…”
Section: Discussionsupporting
confidence: 51%
“…Next, flow cytometric analysis revealed that downregulation of FALEC might contribute to the cell arrest in G1/G0 phase of cell cycle. P21 are family members of cyclin‐dependent kinase inhibitors, which is responsible for arresting cells in G1 phases and negatively control cell proliferation, acting as tumor suppressor . In the present study, cells with down regulation of FALEC leads to increased level of p21 and relative change of downstream CKI and cyclin, indicating that FALEC exerts its oncogenic function at least in part via suppressing of p21 expression.…”
Section: Discussionsupporting
confidence: 51%
“…Further, GUCY2C signaling regulates proliferation and DNA damage repair, processes that are canonically disrupted in RIGS (26). Indeed, signaling through the GUCY2C-cGMP axis inhibits DNA synthesis and prolongs the cell cycle, imposing a G1-S delay in part by regulating p21, key injury responses to radiation (1820,50). Further, silencing GUCY2C increases DNA oxidation and double strand breaks, amplifying mutations induced by chemical or genetic DNA damage, reflecting ROS and inadequate repair (20).…”
Section: Discussionmentioning
confidence: 99%
“…GUCY2C-deficient (Gucy2c 2/2 ) mice exhibit epithelial dysfunction that recapitulates discreet attributes of tumorigenesis, including an expanded proliferating crypt compartment, increased DNA damage, metabolic reprogramming to a Warburg glycolytic phenotype, restricted differentiation and lineage commitment, and amplified oncogenic signaling through changes in p21, Akt, and other pathways (Li et al, 2007b;Rinaldi et al, 2010;Han et al, 2011;Okabayashi et al, 2012). Consistent with its role as a tumor suppressor, intestinal neoplasia in Gucy2c 2/2 mice was substantially increased, compared with wild-type mice, by the chemical carcinogen azoxymethane or by mutations in adenomatous polyposis coli (Li et al, 2007b;Rinaldi et al, 2010;Basu et al, 2014).…”
Section: Gucy2c Signaling and The Paracrine Hormone Hypothesis Of Colmentioning
confidence: 50%